Genetic variants in taste-related genes and risk of pancreatic cancer. (12th October 2019) - Gentiluomo, Manuel; Lu, Ye; Canzian, Federico; Campa, Daniele
Abstract: Pancreatic ductal adenocarcinoma is an aggressive and relatively rare cancer with a dismal 5-year survival rate and a clear genetic background. Genetic variants in taste receptors and taste-related genes have been associated with a variety of human traits and phenotypes among which several cancer types and pancreatic cancer risk factors. In this study, we analysed 2854 single-nucleotide polymorphisms in 50 taste-related genes, including 37 taste receptors. To cover all the genetic variability of the selected genes and to include also regulatory elements, we added 5000 nucleotides to both ends of each gene. We used a two-phase approach, with the PanScan data set (3314 cases and 3431 controls) as the discovery phase and PanC4 (3893 cases and 3632 controls) as validation phase, for a total of 7207 cases and 7063 controls. The datasets were downloaded from the NCBI database of genotypes and phenotypes (dbGaP). We observed that the taste 1 receptor member 2 ( TAS1R2 )-rs11261087 variant was associated with pancreatic cancer risk in both phases independently, with a consistent association of the T allele with decreased risk of developing the disease [phase 1 odds ratio (OR) = 0.89, 95% confidence interval (CI) 0.80–0.98; phase 2 OR = 0.91, 95% CI 0.83–0.99; all subjects together OR = 0.90, 95% CI 0.84–0.96, P = 0.002]. However, neither the association observed in the validation phase nor those observed in the joint analysis were statistically significant considering multiple testing. Functional studies are warranted to better understand the impact of the genetic variability of TAS1R2 on PDAC risk.